2019
DOI: 10.1155/2019/9134096
|View full text |Cite
|
Sign up to set email alerts
|

Endocan Is an Independent Predictor of Heart Failure-Related Mortality and Hospitalizations in Patients with Chronic Stable Heart Failure

Abstract: Background. Heart failure (HF) is characterized by unfavorable prognosis. Disease trajectory of HF, however, may vary, and risk assessment of patients remains elusive. In our study, we sought to determine the prognostic impact of endocan—a novel biomarker of endothelial dysfunction and low-grade inflammation—in patients with heart failure. Methods. In outpatients with chronic HF, baseline values of endocan were determined and clinical follow-up for a minimum of 18 months obtained. A multivariate Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Esm-1 transcription is stimulated by pro-inflammatory cytokines 18 , and progressive DKD is characterized by inflammation 15,[31][32][33][34][35] . Although others have reported correlations of Esm-1 with kidney diseases 23,[36][37][38] , cardiovascular diseases 23,[39][40][41][42] , and cancer [43][44][45][46][47] , data linking Esm-1 to DKD are mixed. For example, Ekiz-Bilir et al showed a direct correlation between serum Esm-1 and the degree of albuminuria in patients with type 2 diabetes mellitus 48 , while Cikrikcioglu et al reported the opposite 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Esm-1 transcription is stimulated by pro-inflammatory cytokines 18 , and progressive DKD is characterized by inflammation 15,[31][32][33][34][35] . Although others have reported correlations of Esm-1 with kidney diseases 23,[36][37][38] , cardiovascular diseases 23,[39][40][41][42] , and cancer [43][44][45][46][47] , data linking Esm-1 to DKD are mixed. For example, Ekiz-Bilir et al showed a direct correlation between serum Esm-1 and the degree of albuminuria in patients with type 2 diabetes mellitus 48 , while Cikrikcioglu et al reported the opposite 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being linked to cardiovascular risk factors, endothelial dysfunction predicts adverse clinical events, and its grade is analogous to the functional capacity and the severity of HF [33]. A recent study of chronic HF patients showed that apart from plasma endocan being elevated compared with healthy controls and patients with coronary artery disease, it emerged as an independent prognosticator of HF-related hospitalization and mortality [35]. In a rat model of PAH, endocan levels were elevated in the serum and lungs, and knockdown of endocan reversed monocrotaline-induced pulmonary vascular remodeling and reduced right-ventricular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were included if they met the following criteria: (i) signs and symptoms of HF at the time of Holter monitoring recording [ 16 ]; (ii) echocardiographic evidence of preserved LVEF (LVEF ≥ 50%) [ 16 ] and structural cardiac abnormalities (hypertrophy, diastolic dysfunction, left atrial enlargement, and/or increased tricuspid regurgitation velocity [ 2 ]; (iii) N-terminal B-type natriuretic peptide (NT-proBNP) level > 600 pg/mL; (iv) preserved sinus rhythm; and (v) stable disease for at least 3 months prior to Holter monitoring recording [ 2 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included (i) an acute cardiovascular event within the past 3 months (e.g., myocardial infarction, stroke, or thromboembolic event) [ 16 ]; (ii) atrial fibrillation or other arrhythmias incompatible with HRT and/or HRV determination; and (iii) significant non-cardiac comorbidities with expected survival < 1 year [ 16 ].…”
Section: Methodsmentioning
confidence: 99%